Sustainable Intensification of Smallholder Farming Systems, adapted to Climate Change, makes inroads with 3 million farmers in southern Africa - CGIAR Research Program on Maize (2021)
Long-term Conservation Agriculture (CA) systems research in Malawi, Zambia and Zimbabwe has generated scientific evidence regarding CA’s productivity, profitability, environmental, social and human impacts. These are widely used by National Governments to adapt policies for more climate-smart agriculture interventions, leading to CA adoption on >627,000 ha and yield benefits of 30-50% (up to 140%) under drought. Due to greater water-use efficiency, applying the principles of CA is effective in reducing climate risks thus reducing the vulnerability of farming communities.